Effect of good village governance implementation in Indonesia - MUNIR, D.A; AKBAR, B; MULYANI, S; MUSA, Y (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to examine the effect of the implementation of good village governance in Indonesia, its competence and performance, based on the level of fraud and its fund management. Data was collected by conducting a survey of 1,080 management-level respondents in village government. The results found that the poor implementation of the good village governance reveal a high level of fraud in the management of funds. This condition was reflected in the lack of equitable development and the failure to alleviate poverty.